Death and beauty: mortality salience and creatureliness increase self-objectification not only in females but also in males - Gao, Yang; Lu, Kexin; Ni, Yichen; Shen, Yang (Frontiers in Psychology, 2025)
BackgroundSelf-objectification, the tendency to perceive oneself as an object subject to external evaluation, negatively impacts wellbeing, contributing to issues such as anxiety and eating disorders. While objectification theory outlines its societal underpinnings, it provides limited insight into the psychological mechanisms that sustain its prevalence. Terror Management Theory (TMT) posits that self-objectification functions as a defense against death anxiety, operating through two pathways: cultural worldview compliance (adherence to objectifying societal norms) and suppressing the awareness of creatureliness (avoiding awareness of humans’ biological vulnerability and animalistic nature). This research explores these mechanisms and their gender-specific dynamics under mortality salience (MS).MethodsThis study includes three experimental studies. The study 1 examined baseline gender differences in perceived creatureliness and adherence to objectification culture. Study 2 used a 2 (MS/control) × 2 (gender: male/female) design to investigate the effects of MS and gender on self-objectification with cultural worldview compliance as a continuous moderator. Study 3 employed a 2 (MS/control) × 2 (creatureliness: heightened/reduced) × 2 (gender: male/female) design to assess the effects of creatureliness salience on self-objectification.ResultsStudy 1 revealed that women were more culturally objectified, whereas men exhibited higher perceived creatureliness. However, Study 2 and Study 3 found no significant gender-related interactions in self-objectification. Study 2 showed that MS increased self-objectification across genders, with women displaying higher self-objectification due to stronger adherence to objectification cultural norms. Study 3 demonstrated that heightened creatureliness salience amplified self-objectification under MS for both genders, highlighting the universal role of creatureliness suppression in existential defenses.ConclusionThese findings provide evidence for dual pathways—cultural worldview compliance and creatureliness suppression—underlying self-objectification as a defense against death anxiety. However, while cultural compliance explains gender differences in self-objectification at baseline, creatureliness suppression appears to function universally across genders. This study clarifies the boundaries of gender differences, emphasizing that the observed gender differences were limited to perceptions of objectification and creatureliness, rather than self-objectification itself. These insights contribute to interventions targeting the maladaptive effects of self-objectification, advocating for gender-sensitive approaches to enhance psychological wellbeing.